EJA e práticas pedagógicas : contribuições e desafios presentes nas publicações da ANPED nos anos de 2003 a 2013 - Gavioli, Aline Vanessa (2015)
This master thesis is guiding question understand what teaching practices that contribute to the care of young people and adults in the classroom from the analysis of the GT 18 ANPEd, which hosts the publications of the EJA, during the years 2010 to 2013. This issue aims to: identify and analyze to what extent the work published in this GT, teaching practice match action proposals for work in adult education rooms, and whether these actions are presented as ruptures and / or processing in student learning. To achieve these objectives was performed a literature search for collection and selection of articles based in Salvador (1986) and the content analysis, based on Bardin (2011). The research analyzed 24 articles, especially the proposals developed from the perspective of design methodology, which were articles that indicated directly practical actions for adult education. In addition, the articles sought the transformer indicated that the dialogic teaching practices and the articulation of knowledge of students with school knowledge, which have their basis in Freire's theory, are those that contribute most to the impact of work in the academic life of subject because facilitate mastery of instrumental knowledge and are also reflected in the social life of students, allowing transformations of relationships and the environment in which the students are inserted.